2021
DOI: 10.3390/insects12080672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diets Including Agro-Industrial By-Products on the Fatty Acid and Sterol Profiles of Larvae Biomass from Ephestia kuehniella, Tenebrio molitor and Hermetia illucens

Abstract: Rearing insects on agro-industrial by-products is a sustainable strategy for the circular economy while producing valuable products for feed and foods. In this context, this study investigated the impact of larvae diet containing agro-industrial by-products on the contents of fatty acids and sterols of Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae), Tenebrio molitor (L.) (Coleoptera: Tenebrionidae), and Hermetia illucens (L.) (Diptera: Stratiomyidae). For each insect, selected diets were formulated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
3
5
1
1
Order By: Relevance
“…6, the total fatty acid concentration in Hermetia illucens larvae was mainly comprised of saturated fatty acids (SFAs) accounting for 65.18 ± 0.18 %, followed by monounsaturated fatty acids (MUFAs; 19.99 ± 0.10 %) and polyunsaturated fatty acids (PUFAs; 14.79 ± 0.07 %). Hermetia illucens contains a high amount of mid-chain fatty acids, with lauric acid being the most abundant, followed by palmitic acid and oleic acid [47,48]. Furthermore, substantial amounts of linoleic acid (C18:2) were observed in this study (13.78 ± 0.07 %) and the result corroborates with the findings from Rabani et al [49] and Mai et al [46].…”
Section: Effect Of Drying On Fatty Acidssupporting
confidence: 92%
“…6, the total fatty acid concentration in Hermetia illucens larvae was mainly comprised of saturated fatty acids (SFAs) accounting for 65.18 ± 0.18 %, followed by monounsaturated fatty acids (MUFAs; 19.99 ± 0.10 %) and polyunsaturated fatty acids (PUFAs; 14.79 ± 0.07 %). Hermetia illucens contains a high amount of mid-chain fatty acids, with lauric acid being the most abundant, followed by palmitic acid and oleic acid [47,48]. Furthermore, substantial amounts of linoleic acid (C18:2) were observed in this study (13.78 ± 0.07 %) and the result corroborates with the findings from Rabani et al [49] and Mai et al [46].…”
Section: Effect Of Drying On Fatty Acidssupporting
confidence: 92%
“…Since the EU (Commission Regulation (EU) 2017/893) [ 27 ] permitted the use of larval insect meal (e.g., black soldier fly Hermetia illucens and yellow mealworm Tenebrio molitor ) for aquafeed in 2017, several studies on H. illucens and T. molitor have shown that there are no side effects on the growth performance of European seabass at inclusion rates of 20–30% [ 28 30 ]. However, the fatty acid content of insect meal can vary depending on the composition of the substrate and developmental stage of the insect, though it mostly depends on insect species, e.g., H. illucens is rich in n-3 polyunsaturated fatty acids, whereas T. molitor is abundant in n-6 polyunsaturated fatty acids [ 31 ]. Consequently, the choice of insect meal used in the fish diet can affect the whole-body fatty acid composition of fish [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these wastes are rich in bioactive compounds such as vitamins, carotenoids, and minerals (Barcelos et al, 2020). Therefore, developing sustainable solutions to reuse and recycle AIBPs will be essential for economic and environmental prospects (Boukid et al, 2021;Sadh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%